High prevalence of hepatitis B infections in Burkina Faso (1996-2017): a systematic review with meta-analysis of epidemiological studies - Moussa Lingani; Tomoyuki Akita; Serge Ouoba; Armel Moumini Sanou; Aya Sugiyama; Zekiba Tarnagda; Masayuki Ohisa; Halidou Tinto; Shunji Mishiro; Junko Tanaka (BMC, 2018)
Abstract Background Hepatitis B virus (HBV) infection was long considered an important public health concern in Burkina Faso and still represents a major cause of liver cancer and cirrhosis in the active population. To counter the problem, a national strategic plan was developed and adopted in July 2017 to coordinate viral hepatitis elimination's efforts. However evidence to support its implementation remains scanty and scattered. The main purpose of this study was to summarize available information from per-reviewed articles published over the last two decades to accurately estimate the prevalence of HBV infection in Burkina Faso. Methods We conducted a systematic search with meta-analysis of scientific articles using Science-Direct, Web-of-Science, PubMed/Medline, and Google Scholar. We systematically assessed all relevant publications that measured the prevalence of hepatitis B surface antigen and which were published between 1996 and 2017. We estimated the national HBV prevalence and its 95% confident interval. We subsequently adjusted the meta-analysis to possible sources of heterogeneity. Results We retrieved and analyzed a total of 22 full text papers including 99,672 participants. The overall prevalence was 11.21%. The prevalence after adjustment were 9.41%, 11.11%, 11.73% and 12.61% in the general population, pregnant women, blood donors and HIV-positive persons respectively. The prevalence was higher before implementation of HBV universal vaccination and decreased from 12.80% between 1996 and 2001 to 11.11% between 2012 and 2017. The prevalence was also higher in rural area 17.35% than urban area 11.11%. The western regions were more affected with 12.69% than the central regions 10.57%. The prevalence was 14.66% in the boucle of Mouhoun region and 14.59 in the center-west region. Aggregate data were not available for the other regions. Conclusions HBV has clearly an important burden in Burkina Faso as described by its high prevalence and this problem significantly challenges the national health care system. There is an urgent need for effective public health interventions to eliminate the problem. However, higher quality data are needed to produce reliable epidemiological estimates that will guide control efforts towards the achievement of the national strategic plan's goals.